Entrepreneurship as the Creation of the New Capital - SMIRNOV, Vladimir P. (Journal of Advanced Research in Law and Economics; Vol 7 No 8 (2016): JARLE Volume VII, Issue 8(22), Winter 2016, 2017)
The article discusses various approaches to the study of entrepreneurship. The most significant characteristics of the entrepreneurship identified. Integrative approach was applied in the study of entrepreneurship. On this basis it was concluded that entrepreneurship is an innovative, accompanied by the risk activity of economic agents aimed at the creation of new capital and to receive of various forms of entrepreneurial income on this basis. The new capital is created in various forms of productive, financial and intellectual types of capital. The new capital in a variety of types and forms is both a factor and a result of the development of entrepreneurship. Intellectual capital is becoming the dominant form of capital in the post-industrial society. New knowledge about entrepreneurship allowed to bring together different ideas about it. They allowed defining more precisely the process of creating entrepreneurial organizations to measure and evaluate the level of development of entrepreneurship in different sectors of the economy. It is shown that the efforts of specialists should be directed to study ways to create various forms of new capital.